Fungi-Bacteria Associations in Wilt Diseased Rhizosphere and Endosphere by Interdomain Ecological Network Analysis - Tan, Lin; Zeng, Wei-ai; Xiao, Yansong; Li, Pengfei; Gu, Songsong; Wu, Shaolong; Zhai, Zhengguang; Feng, Kai; Deng, Ye; Hu, Qiulong (Frontiers in Microbiology, 2021)
In the plant rhizosphere and endosphere, some fungal and bacterial species regularly co-exist, however, our knowledge about their co-existence patterns is quite limited, especially during invasion by bacterial wilt pathogens. In this study, the fungal communities from soil to endophytic compartments were surveyed during an outbreak of tobacco wilt disease in China. It was found that the stem endophytic fungal community was significantly altered by pathogen invasion in terms of community diversity, structure, and composition. The interactions among fungal species in the rhizosphere and endosphere infected by bacterial wilt showed more complex network structures than those of healthy plants. By integrating the bacterial dataset, interactions between fungal and bacterial species were inferred by Inter-Domain Ecological Network (IDEN) approach. It also revealed that infected samples, including both the rhizosphere and endosphere, had more complex interdomain networks than the corresponding healthy samples. Additionally, the bacterial wilt pathogen Ralstonia was identified as a keystone species within the IDENs of both root and stem endophytic compartments. Ralstonia was negatively correlated with species of the fungal genera Phoma, Gibberella, and Alternaria in infected roots, as well as Phoma, Gibberella, and Diaporthe in infected stems. This suggested that those endophytic fungi may play an important role in resisting the invasion of tobacco bacterial wilt.